The Irish Catholic Church under Charles II: the ‘Popish Plot’ and the Martyrdom of Oliver Plunkett - Marie-Claire Considère-Charon (Revue Française de Civilisation Britannique)
The late 1670s under Charles II were a special time in British history during which religious controversy ran high. The rivalry between the king, who issued a Declaration of Indulgence suspending all laws punishing Roman Catholics and other religious dissenters, and a strongly Anglican Parliament had reached its peak. In Ireland the Catholic Church had slowly been recovering from the Cromwellian persecution when Pope Clement IX decided to appoint Oliver Plunkett as Archbishop of Armagh. His mission was to rebuild and reform the Catholic Church in Ireland. Fears of a return to Catholicism in England were exacerbated by allegations by Titus Oates of a ‘Popish Plot’ to murder Charles II and establish absolutist, Catholic government under James, Duke of York and the king’s brother. Oliver Plunkett, after a blatant miscarriage of justice, was executed for high treason. He was beatified in 1920 and canonized in 1975 under Pope Paul VI. Without going so far as to deconstruct hagiographical narratives, which made Plunkett the Irish Church’s most celebrated martyr, this article focuses on the political and religious stakes during a troubled period when the destinies of the English and Irish nations and their Churches were not yet clearly mapped.